THE GEOCHEMISTRY OF SHALES FROM THE “FRIDO UNIT”, LIGURIDE COMPLEX, LUCANIAN APENNINES, ITALY: IMPLICATIONS FOR PROVENANCE AND TECTONIC SETTING - Mongelli, Giovanni; Dinelli, Enrico (Ofioliti, 2001)
The geochemistry of shales from a well-exposed section in the “Frido Unit” located in the Lucanian Apennine is discussed to contribute on both provenance affinity and tectonic history of the terranes which accreted in the Liguride wedge in the Western Mediterranean area. The distribution of major and trace elements in these shales is close to the average composition of the Post Archean Australian Shales, (i.e, of upper crustal derived fine-grained sediments). Geochemical proxies of provenance including REE, HFSE and Sc, V and Cr, as inferred by R-mode statistical analysis, are linked to detrital minerals, (i.e., clay phases), supporting the idea they efficiently record source area composition. Other transition elements including Co, Ni, Cu and Zn covariate with S, Pb and Sb suggesting they are principally housed in sulphur minerals. It, in turn, involves these TE and especially Co, an element retained as an important provenance indicator, have to be used with care to assess parental affinity for Frido shales.The weathering in the source area, estimated using the CIA index, was moderate. This is consistent with the values of Th/U index and the content of total REE in the rocks, which are only slightly higher than the average shale. These indices, as well as the Zr/Sc ratio indicate, the role of sediment recycling was minor. The role of sorting on the variations of Eu/Eu*, REE, Th and possibly Sc is negligible.In the La-Th-Sc plot the Frido shales fall close to the average composition of continent-derived material consistent with the values of the Eu/Eu* index. Upper crustal provenance, excluding significant mafic supply, is highlighted also using the Cr/V vs Y/Ni and Fe/Ti vs Al/(Al+Fe+Mn) plots. The La-Th-Sc plot indicates that Frido shales fall in the field of continental arc whereas the deposition of the sediment occurred in a tectonic setting related to an active continental margin and the same result is obtained using the Th-Sc Zr/10 plot. Discrimination diagrams likely describe the paleotectonic setting of the source and not that of the basin in which the sediment was deposited.